A clinical study to evaluate therapeutic efficacy of soft contact lenses in corneal diseases - Punjabi, Sharda; Bedi, Nutan (International Journal of Research in Medical Sciences, 2016)
Background: Therapeutic contact lenses have a wide range of uses. This study was planned to evaluate therapeutic efficacy of soft contact lenses in various corneal diseases for providing and promoting relief of pain, epithelial healing, protection, improving visual acuity. Methods: This study was conducted in ophthalmology department of a tertiary care teaching hospital after taking permission from the institutional ethics committee. Before subjecting the patient to treatment of therapeutic hydrophilic contact lens therapy for various corneal diseases, a detail clinical history and thorough local examination and certain investigations were performed and treatment given for each condition was standard. Evaluation of patient was done daily in admitted patients and after 3 days in discharge patients, then weekly for first month then follow up was done depending on underlying condition; maximum for 6 months. Patients were monitored for amelioration of signs and symptoms, improvement in visual acuity and slit lamp examination finding and change in intraocular pressure was also recorded. Results: Total 50 enrolled cases were divided in eight groups. Improvement in patients was 70% for bullous keratopathy group, 80% (Corneal perforation and descemetocoel group), 70% (corneal ulcer group), 40% (dry eye syndrome group), 66.67% (lid abnormalities group), 100% (filamentary keratitis and superior limbic keratoconjunctivitis group), 66.67% (recurrent corneal erosion group), and 100% in drug delivery group. Superficial corneal neovascularisation (10%) was found more common complication followed by infectious keratitis (6%) and lensopathy (4%). Conclusions: Soft contact lenses can be safely advocated as a part of therapy along with adjuvant conventional management with well expected improvement in the ocular corneal diseases.